Development and Implementation of Evaluation Rubric on Electronics Practical Skills in TVET Programme for Industrial Relevance - Fidelia; Okoye (Journal of Research in Industrial Technology and Educational Studies, 2026)
The study determined the needed techniques on the development and implementation of evaluation rubrics on electronics practical skills in TVET programme for industrial relevance- construction and testing of single stage transistor amplifier circuit. The study answered three research questions and two hypotheses. Descriptive survey was adopted to carry out the research in Imo State. The population of study was 45 respondents, comprising of 26 Electronics Education Lecturers and 19 Electronics Engineering Technology Lecturers from high institutions in the State. There was no sampling due to smallness of the population, an intact population was used. A 23 – item questionnaire titled, ‘Development and Implementation of Evaluation Rubrics on the, ‘Construction and Testing of a Single Stage Transistor Amplifier Circuit’(DIER-AMP) was used for data collection; which was validated by three experts. The reliability of the instrument was 0.81 established using Cronbach Alpha. The questionnaire items were generated from the review of the related literature.  Out of 45 questionnaires administered, 44 of them were returned. Mean and standard deviation were used to answer the research questions and null hypotheses were tested at 0.05 level of significance using Z-test. Mean of 3.50 or above was considered for the agreed items. Result of study revealed 5 agreed considerations, 8-items were the agreed process skills evaluation rubric; 8- items were the agreed product-skills evaluation rubric. Consequently, it was recommended that, electronic components, materials, tools and instruments should be provided in the workshop for learning practical skills and 50% of assessment in exam questions for each level in electronics should be based on practical. Collaboration should exist with experts from electronics industries in the teaching and evaluation of students to meet the expected standard among others.
Keywords: Electronics; Electronics practical skills; Evaluation; Evaluation rubrics; TVE